Influência do tratamento químico na pozolanicidade de micropartículas de vidro soda-cal usadas em sistemas de cimento - Correia, João Victor Freitas Barros (2024)
The environmental problems linked to the consumption of Portland cement mean that alternatives are increasingly sought to reduce its impacts. The use of waste with pozzolanic properties is a promising alternative to reduce the impacts of Portland cement production. The use of chemical treatments on pozzolanic materials proves to be effective in making the incorporation of supplementary cementitious materials (MCS) into cement systems more efficient. Therefore, this research aims to analyze the effect of chemical treatment on soda-lime glass. packaging in its pozzolanic properties. A treatment was carried out on 3 different particle size fractions of glass particles (<75 µm, <45 µm and <25 µm) in a saturated calcium hydroxide solution at a temperature of 80 °C for 7 days. The effect of the chemical treatment on the morphology of the particles was evaluated by laser granulometry and SEM/EDS, later mortar test specimens were prepared following ABNT NBR 5751 and ABNT NBR 5752 to be evaluated by compressive strength, additionally, pastes with a composition equivalent to mortars to be investigated by XRD, TG/DTG and SEM/EDS focusing mainly on the C-S-H, CH and CaCO3 phases. The results show that the treatment formed C-S-H on the surface of the glass microparticles, which contributed to the formation of agglomerates thereof, and that when incorporated into cementitious systems, the chemically treated particles present greater pozzolanic activity than the untreated particles.